2023
DOI: 10.3390/antiox12051131
|View full text |Cite
|
Sign up to set email alerts
|

Pros and Cons of Dietary Vitamin A and Its Precursors in Poultry Health and Production: A Comprehensive Review

Abstract: Vitamin A is a fat-soluble vitamin that cannot be synthesized in the body and must be obtained through diet. Despite being one of the earliest vitamins identified, a complete range of biological actions is still unknown. Carotenoids are a category of roughly 600 chemicals that are structurally related to vitamin A. Vitamin A can be present in the body in the form of retinol, retinal, and retinoic acid. Vitamins are required in minute amounts, yet they are critical for health, maintenance, and performing key bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 117 publications
0
2
0
Order By: Relevance
“…In this way, VA is crucial for maintaining bird fertility ( Yaripour et al, 2018 ). Similarly, Khan et al (2023) reported that VA supplementation in poultry supports growth, feed efficiency, egg production, quality, immunity, hatchability, and congenital malformations.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In this way, VA is crucial for maintaining bird fertility ( Yaripour et al, 2018 ). Similarly, Khan et al (2023) reported that VA supplementation in poultry supports growth, feed efficiency, egg production, quality, immunity, hatchability, and congenital malformations.…”
Section: Discussionmentioning
confidence: 97%
“…Fat-soluble vitamins, including VA, are a micronutrient necessary for immune system upkeep, embryonic growth, epithelial tissue integrity, and reproduction in chickens ( Yuan et al, 2014 ; Chen et al, 2016 ; Khan et al, 2023 ). The embryonic development of birds is positively impacted by the VA stored in the liver and egg yolk ( O'Byrne and Blaner, 2013 ; Ebeid et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…The essential role of vitamin A in poultry vision stems from its multiple important functions [2]. One of its primary roles is to support and maintain overall eye [75].…”
Section: The Crucial Contributions Of Vitamin A: Metabolism Growth Im...mentioning
confidence: 99%
“…Among the many essential micronutrients, vitamins play a crucial role in supporting vital physiological functions. Understanding the significance of vitamins, particularly vitamin A (retinol), in poultry health and productivity is paramount for optimizing poultry management practices [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation